CLEAR design: developing an electronic copyright management system for Project ACORN. - Gadd E; Goodman R; Muir A (Electronic Library, 1998)
Outlines the copyright clearance difficulties faced by librarians in the development of the Electronic Library and states the need for an electronic copyright management system (ECMS) to log the clearance process and to protect electronic documents. Reports the absence of a suitably priced commercially available ECMS for the academic sector and describes the design process for the eLib project ACORN's Rights Management system entitled CLEAR (Copyright Licensed Electronic Access to Readings) based on Microsoft Access. Describes the functionality of the CLEAR database and concludes that it might provide a template for other institutions in the design of subsequent ECMSs.